Benefits of usage of new information technologies in the learning process. (Eurasian Journal of Philology Science and Education, 2015)
This article discusses the methods of using new information technologies in the learning process and benefits of innovation and information technology, which are the main factor in improving the quality of education. Informationtechnologies are implemented through e-learning. E-learning tools - software tools that reflect a certain subject area, in one way or another technology is implemented study by means of information and communication technologies,to provide for the implementation of the various types of training activities.
Keywords: to inform; information technology; E-learning tools